Activation of the hypoxia‐inducible factor pathway induced by prolyl hydroxylase domain 2 deficiency enhances the effect of running training in mice. (25th July 2016) - Nunomiya, A.; Shin, J.; Kitajima, Y.; Dan, T.; Miyata, T.; Nagatomi, R.
Abstract: Aims: Hypoxic response mediated by hypoxia‐inducible factor (HIF) seems to contribute to the benefit of endurance training. To verify the direct contribution of HIF activation to running training without exposure to atmospheric hypoxia, we used prolyl hydroxylase domain 2 (PHD2) conditional knockout mice (cKO), which exhibit HIF activation independent of oxygen concentration, and we examined their maximal exercise capacity before and after 4 weeks of treadmill exercise training. Methods: Phd2 f/f mice ( n  = 26) and Phd2 cKO mice ( n  = 24) were randomly divided into two groups, trained and untrained, and were subjected to maximal running test before and after a 4‐week treadmill‐training regimen. Results: Prolyl hydroxylase domain 2 deficiency resulted in HIF‐α protein accumulation. Phd2 cKO mice exhibited marked increases in haematocrit values and haemoglobin concentrations, as well as an increase in the capillary number in the skeletal muscle. The 4‐week training elicited an increase in the capillary‐to‐fibre (C/F) ratio and succinyl dehydrogenase activity of the skeletal muscle. Importantly, trained Phd2 cKO mice showed a significantly greater improvement in running time than trained control mice ( P  <   0.05). Collectively, these data suggest that the combination of training and the activation of the HIF pathway are important for maximizing the effect of running training. Conclusion: We conclude that the activation of the HIF pathway induced by PHD2 deficiency enhances the effect of running training.